THE STRENGTHS AND DRAWBACKS OF LYRICSTRAINING IMPLEMENTATION IN BASIC LISTENING COURSE - Patricia Angelina (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2020)
Development in ICT has resulted in innovations in terms of new applications and software to use in education, one of them is in the English language teaching. This study aims to find out the strengths and drawbacks of LyricsTraining implementation as one example of the web-based CALL in the Basic Listening course, one of the obligatory courses in the English Language Education Study Program of Sanata Dharma University. LyricsTraining is a website that integrates audio and video taken from YouTube with the song lyrics. It allows the students to play the music video and requires them to type in the missing lyrics or choose from the options provided. Survey was used as the method of this study, involving 30 first semester students from one class of Basic Listening course as the participants. Questionnaire with close and open-ended questions was used to gather the data. The results of this study describe the strengths as well as the drawbacks of the implementation of LyricsTraining in the Basic Listening course experienced by the students.